Four-pronged Brackets - Ghosh, Ayan (2023)
Over the years, St. Thomas Church has been upgraded with the change in technology and the need for improving public convenience. For example, wrought iron brackets were fitted to the pillars when electricity was introduced for the first time in 1907. Fans and lights hang from the ends of each bracket, providing comfort to the congregation assembled in the hall.